Two Models of Child Labour in the Past - Łukasiewicz, Dariusz (Studia Historiae Oeconomicae, 2023)
Nowadays we perceive child labour as a shameful torture and a wicked destruction of the natural order of things. After all, childhood is a time for carelessness, fun and schooling, and children are innocent and vulnerable. Nowadays people believe that these are primeval and natural rights, which is not true. There used to be two models of child labour which I present in my paper. Domestic work in the countryside and in cities, characteristic of the feudal economy at the time when a workplace and a place of residence were the same place (this is still the case in the countryside nowadays), and work outside home, for example in a factory, characteristic of the capitalist economy. There were also varied mixed forms. Thus, in the pre-modern period, rural children were already given to work on a lord’s farm, to a rich farmer, or to serve in a city. Similarly, in modern times, children worked at home in domestic industries. The extensive use of child labour was first made possible by the lack of compulsory schooling, which in turn later prevented regular child labour. As long as there was an economic need, however, school had to give way to earning a living for one’s family.